The role of organ-deposited IgG in the pathogenesis of multi-organ and tissue damage in systemic lupus erythematosus - Qiu, Wenlin; Yu, Tong; Deng, Guo-Min (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE), often known simply as lupus, is a severe chronic autoimmune disease that is characterized by multi-organ and tissue damage and high levels of autoantibodies in serum. We have recently investigated, using animal models, the role of organ-deposited IgG autoantibodies in the pathogenesis of organ and tissue damage in SLE. We found that intra-organ injection of serum from mice with lupus (i.e., lupus mice) into healthy mice triggered inflammation in tissue and organs but that serum from other healthy mice did not, and that the severity of inflammation was related to the dose of serum injected. Immunohistochemistry showed that a large number of IgG molecules are deposited at the site of organ and tissue damage in lupus mice, and that IgG is a major contributor to the development of tissue inflammation triggered by serum from lupus mice or patients. The development of tissue inflammation induced by IgG in serum from lupus mice requires the presence of monocytes/macrophages, but not of lymphocytes or neutrophils; tumor necrosis factor (TNF)/tumor necrosis factor receptor 1 (TNFR1) and interleukin 1 (IL-1) also play essential roles in the development of tissue inflammation triggered by IgG. In addition, it has been found that TNFR1 inhibitors can suppress skin injury in lupus mice and that spleen tyrosine kinase (Syk) inhibitors, which can block the signaling transduction of IgG/Fc gamma receptors (FcγRs), can prevent and treat skin injury and kidney damage in lupus mice. We have also observed that lupus IgG might protect against bone erosion. Based on these results, we conclude that IgG plays a crucial role in the development of organ and tissue damage in SLE and in protecting bone erosion and arthritis, and we suggest that the IgG/FcγR signaling pathway is an important therapeutic target in SLE.